Bedhaya Bedhah Madiun Dance As A Tourism Asset In Pura Mangkunagaran - Kristiyanti, Dewi; Widyastuti, Mamik; Maryani, Dwi; bin Said, Fathurrahman (Gelar: Jurnal Seni Budaya, 2022)
The research objective of Bedhaya Bedhah Madiun Dance as a Tourism Asset in Pura Mangkunagaran is a tourism asset that can provide foreign revenue for the Mangkunagaran family. This research uses descriptive analysis by using qualitative approach. The data collection technique was done by observing, interviewing and documenting. The results showed that Bedhaya Bedhah Madiun Dance is an artistic attraction that can be packed in a compact and concise manner where its sacred value is removed into an entertaining performance and presented to domestic and foreign tourists, so it has economic value for Pura Mangkunagaran. Bedhaya Bedhah Madiun dance is a tourist asset, performed in several places with different audiences as well as an interesting dance attraction. Bedhaya Bedhah Madiun dance is composed by new dance movements even though they still using few traditional patterns. The dance movements of the new arrangement are following to the ability of the dancers who are concerned to be entertaining and attractive for tourism. Floor patterns, make-up and dress and dance accompaniment are laid out to support the performance.